A creative model for integrating the identity of Dalian Chinese painting into cultural product design - Weijian, Yuan; Khiatthong, Thongchue (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to develop and validate a creative model that integrates the identity of Dalian Chinese painting into cultural product design, focusing on embedding local artistic characteristics into modern innovation. A mixed-methods design was applied across three phases: (1) extraction of artistic identity through a literature review, visual analysis, and expert interviews; (2) integration into product design via co-creation workshops; and (3) validation using surveys from 100 consumers and 10 experts to assess cultural value, innovation, and market appeal. The results revealed that the prototypes successfully embodied Dalian’s maritime symbolism, oceanic colours, and hybrid brushwork, achieving high ratings in Cultural Identity (M = 4.52), Aesthetic Innovation (M = 4.38), and Market Appeal (M = 4.32). This study confirms that artistic heritage can be systematically integrated into design innovation through a structured creative model, thereby enhancing both theoretical understanding and practical outcomes of the design process. Designers and cultural enterprises can apply this model to develop culturally distinctive products that enhance regional branding and contribute to the growth of sustainable creative industries.